PENERAPAN SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) UNTUK PENINGKATAN KUALITAS TIDUR LANJUT USIA DI PANTI SOSIAL POTROYUDAN JEPARA - Icca Narayani Pramudyaningsih; Jaka Ahmad Chilman Erlangga; Anita Listyani (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2026)
Poor sleep quality is one of the common problems often experienced by the elderly, which can impact their physical and psychological health, and this condition requires serious attention. Poor sleep quality in the elderly is caused by increased sleep potential, decreased sleep efficiency, and waking up early due to the aging process. Pharmacological approaches typically use medications such as benzodiazepines, sedative-hypnotic drugs that provide quick effects but are dangerous if used long-term, whereas non-pharmacological approaches to insomnia or sleep difficulties include aromatherapy, warm baths, consistent exercise, magnetic field therapy, cupping therapy, acupuncture, and Spiritual Emotional Freedom Technique (SEFT) therapy. SEFT therapy is an intervention method that combines spiritual awareness techniques with stimulation of energy points on the body to address emotional disturbances and increase relaxation. This study aims to determine the effectiveness of SEFT therapy in improving sleep quality in the elderly. The method used was a pre-experimental design with a one-group pretest-posttest. The research subjects were elderly individuals with moderate sleep disturbances. SEFT intervention was conducted over 3 days for 15 minutes with 15 respondents. The results showed a significant increase in sleep quality after SEFT therapy, indicated by a decrease in sleep disturbance scores and an increase in sleep duration and subjective sleep quality of the elderly. Thus, SEFT therapy can be used as an effective and easily applicable non-pharmacological intervention alternative to help improve sleep quality in the elderly.